MENDESAIN KATA-KATA KREATIF BERNILAI JUAL BERMUATAN KEARIFAN BUDAYA JAMBI SEBAGAI BAHAN AJAR PENGEMBANGAN INDUSTRI KREATIF BERBASIS BAHASA - Eddy Pahar Harahap; Yusra D; Akhyarudin Akhyarudin (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the development of students' ability to design creative words with cultural wisdom. The source of research data is the ability to string creative words together and design a setting for words with Jambi cultural wisdom. Data analysis techniques were collected with creative, unique, interesting, and valuable words. The analysis of ability data was carried out individually and then analyzed based on the average percentage value of making a series of creative words and designing a word background of Jambi cultural wisdom. The results of the study can be stated as follows: the ability of each student and group to assemble words and design the background of Jambi cultural wisdom is at the level of 'good' ability, and the ability of sales strategies and sales targets is generally 'very good'. Thus, it is suggested, this learning can be a reference for students interested in language-based creative industries.